Analysis the Effect of Control Valve Opening on Loading Crude Glycerine Water Pump Motor At PT. Unilever Oleochemical Indonesia - Brid, Dwiki Darma Nuriono; Tharo, Zuraidah; Wibowo , Pristisal (CV. Science Tech Group, 2025)
In the palm oil industry, three-phase induction motors have a very important role in the production process. One of the problems that arises is the quality of the loading power on the motor which can make the motor performance less than optimal. In this study, an analysis and calculation of the power of a three-phase induction motor were carried out with the condition of opening the control valve in stages from 0% to 100%. The motor to be discussed is a three-phase induction motor that works as a pump driver for transferring crude glycerine water to the tank farm at the fatty acid 2 plant at PT. Unilever Oleochemical Indonesia. By using the observation method in conducting research to obtain measurement data, the variables taken are changes in current, power factor, and input power. From the results of this study, the output power value and power efficiency on the motor were obtained when the valve was opened 0%-100%, at the highest valve opening of 100%, the motor output power was 4.39 KW with a power efficiency on the motor of 95%, at the lowest valve opening, the motor output power was 3.22 KW with an efficiency value obtained 95%.